Unveiling the contemporary progress of graphene-based nanomaterials with a particular focus on the removal of contaminants from water: a comprehensive review - Assad, Humira; Lone, Imtiyaz Ahmad; Kumar, Alok; Kumar, Ashish (Frontiers in Chemistry, 2024)
Water scarcity and pollution pose significant challenges to global environmental sustainability and public health. As these concerns intensify, the quest for innovative and efficient water treatment technologies becomes paramount. In recent years, graphene-based nanomaterials have emerged as frontrunners in this pursuit, showcasing exceptional properties that hold immense promise for addressing water contamination issues. Graphene, a single layer of carbon atoms arranged in a hexagonal lattice, exhibits extraordinary mechanical, electrical, and chemical properties. These inherent characteristics have led to a surge of interest in leveraging graphene derivatives, such as graphene oxide (GO), reduced graphene oxide and functionalized graphene, for water treatment applications. The ability of graphene-based nanomaterials to adsorb, catalyze, and photocatalyze contaminants makes them highly versatile in addressing diverse pollutants present in water sources. This review will delve into the synthesis methods employed for graphene-based nanomaterials and explore the structural modifications and functionalization strategies implemented to increase their pollutant removal performance in water treatment. By offering a critical analysis of existing literature and highlighting recent innovations, it will guide future research toward the rational design and optimization of graphene-based nanomaterials for water decontamination. The exploration of interdisciplinary approaches and cutting-edge technologies underscores the evolving landscape of graphene-based water treatment, fostering a path toward sustainable and scalable solutions. Overall, the authors believe that this review will serve as a valuable resource for researchers, engineers, and policymakers working toward sustainable and effective solutions for water purification.